Identity and similarity in repetition deafness - Núria Sebastián; Salvador Soto (Psicológica, 2002)
The repetition blindness (RB) and repetition deafness (RD) effects
demonstrate that repeated objects are more difficult to notice than unrepeated
ones when presented within rapid streams of stimuli. Previous research has
shown that RB can occur even if two visual targets are similar but not
completely identical. In the present study we investigated RD for similar
non-identical auditory targets. In Experiment 1 we compared recall
performance for similar target pairs to that for identical target pairs and found
that the difference (the RD) was significantly smaller than when comparing
recall performance for unrelated target pairs to that for identical target pairs.
In Experiment 2 we presented similar, identical and unrelated target pairs in a
within-participants design and confirmed that RD occurs for similar targets
but to a lesser extent than it does for identical targets. In both experiments,
the influence of response biases and lexical competition effects were
minimized so as to render the explanation of the results clear in terms of
pure perceptual processes. The data reported here support models that predict
perceptual RB and RD between similar items, as opposed to other accounts
that predict RB and RD only for items sharing the same identity.